2023
DOI: 10.3389/fcimb.2023.1152349
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disorders of the intestinal microbiota and heart failure in infants with congenital heart disease

Abstract: PurposeThere is a close relationship between the intestinal microbiota and heart failure, but no study has assessed this relationship in infants with congenital heart disease. This study aimed to explore the relationship between heart failure and intestinal microbiota in infants with congenital heart disease.MethodsTwenty-eight infants with congenital heart disease with heart failure admitted to a provincial children’s hospital from September 2021 to December 2021 were enrolled in this study. A total of 22 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The disordered intestinal microbiota in HF patients is mainly characterized by an increase in pathogenic bacteria and a decrease in beneficial bacteria, which aggravate the intestinal inflammatory reaction and increase the levels of intestinal inflammatory factors and toxin secretion [ 16 18 ]. Our previous study revealed that heart failure in infants with congenital heart disease dysregulated the intestinal microbiota, which was characterized by an increase in pathogenic bacteria, a decrease in beneficial bacteria, and decreases in diversity and richness [ 19 ]. This study further examined the relationship between heart failure and intestinal inflammation in infants with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The disordered intestinal microbiota in HF patients is mainly characterized by an increase in pathogenic bacteria and a decrease in beneficial bacteria, which aggravate the intestinal inflammatory reaction and increase the levels of intestinal inflammatory factors and toxin secretion [ 16 18 ]. Our previous study revealed that heart failure in infants with congenital heart disease dysregulated the intestinal microbiota, which was characterized by an increase in pathogenic bacteria, a decrease in beneficial bacteria, and decreases in diversity and richness [ 19 ]. This study further examined the relationship between heart failure and intestinal inflammation in infants with CHD.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Furthermore, another study observed similar characteristics in the gut microbiota of CHD- HF patients compared to CCHD, with a significant increase in Enterococcus abundance and a decrease in Bifidobacteriaceae abundance compared to the control group. 31 These findings suggest that when there is severe impairment of cardiac function in young children, the intestines may experience ischemia or congestion, leading to reduced oxygen supply, increased acidity in the intestinal microenvironment, 32 and thus leading to distinct alterations in the gut microbiota.…”
Section: From Birth To Infantmentioning
confidence: 99%
“… Stage High incidence age CVDs Characteristics of gut bacteria Study object Ref. From birth to infant 0 year old CHD Bifidobacteriaceae, Lactobacillus ↓ CHD mothers 27 Bifidobacteriaceae ↓ Enterococcus ↑ CCHD patients 30 Enterococcus ↑ Bifidobacteriaceae ↓ CHD-HF patients 31 Child and adolescent ≤5 KD Lachnospiracea _ incertae _ sedis , Bacteroides , Blautia ↓ Escherichia _ Shigella , Bifidobacterium , Enterococcus ↑ KD patients 63 Fecal bacillus , Roseburia ↓ KD patients 64 5–18 years old T1DM Streptococcus thermophilus and Lactococcus lactis ↓ Bifidobacteriaceae ↑ T1DM pre onset patients 71 Actinobacteria , Firmicutes ↓ Bacteroidaceae ↑ Lactobacillus , Bifidobacterium , Blautia cocoides / Euberium rectale group, Prevotella ↓ Clostridium , Bacteroide...…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The decreased composition of certain probiotics may affect fetal development through impaired gut barrier, chronic inflammation, and insulin resistance [ 61 ]. The disorder of gut microbiome and metabolism was observed in patients with CHD and heart failure, which was characterized by decreasing microbiome diversity, richness, and downregulation of retinol metabolism [ 62 ]. The serum level of bile acids in patients with repaired Tetralogy of Fallot (TOF) has a positive correlation with indexed right ventricular end‐diastolic volume, which may suggest impaired liver function due to right ventricular dysfunction and systemic congestion [ 63 ].…”
Section: Microbiome Metabolites and Cardiovascular Diseasesmentioning
confidence: 99%